Masoński kod w twórczości Władimira Nabokowa. Próba interpretacji powieści „Zaproszenie na egzekucję” w kluczu symboliki masońskiej - Kortus, Nadzieja (Studia Rossica Posnaniensia, 2016)
This article is an attempt to interpet a work by Vladimir Nabokov, Invitation to a Beheading, with the most important determinants of Masonic culture. There are few studies that discuss this outstanding prose writer in terms of freemasonry and the author of this article discusses this issue with particular attention to the symbolism  of the Masonic initiation ritual.